Oral lichen planus: An update on etiology, pathogenesis, clinical presentation, diagnosis and management - Sonia Gupta; Manveen Kaur Jawanda (Wolters Kluwer Medknow Publications, 2015)
The mouth is a mirror of health or disease, a sentinel or early warning system. The oral cavity might well be thought as a window to the body because oral manifestations accompany many systemic diseases. In many instances, oral involvement precedes the appearance of other symptoms or lesions at other locations. Oral lichen planus (OLP) is a chronic mucocutaneous disorder of stratified squamous epithelium of uncertain etiology that affects oral and genital mucous membranes, skin, nails, and scalp. LP is estimated to affect 0.5% to 2.0% of the general population. This disease has most often been reported in middle-aged patients with 30-60 years of age and is more common in females than in males. The disease seems to be mediated by an antigen-specific mechanism, activating cytotoxic T cells, and non-specific mechanisms like mast cell degranulation and matrix metalloproteinase activation. A proper understanding of the pathogenesis, clinical presentation, diagnosis of the disease becomes important for providing the right treatment. This article discusses the prevalence, etiology, clinical features, oral manifestations, diagnosis, complications and treatment of oral LP.